The Impact of a City’s Brand on Creative Worker’s Choice of Residence - Nursilah Nursilah; Reza Yonatan Hanata; Merrysa Christina; Rd. Nia Kania Kurniawati; Leo Nardo Setia Budi Djojo (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
Technological developments have led to the transfer of occupants from one place to another on the grounds of finding a better place to live. Both at the state and city level, try to attract people to be able to live in their area. One of the steps used to be able to attract this community is to use branding. This research will be carried out to look at the implications of city branding for people’s choices in choosing a place to live, especially creative workers. This research will be carried out using a qualitative approach. This research data comes from the research results and previous studies that still have similarities with this research. The results of this study indicate that branding a city as a smart city considerably influences creative workers in determining their place of residence. This is because the existence of a smart city through its dimensions helps creative workers in their daily life and work.